Time characteristics of karate practitioners’ technical movements during the preliminary basic training phase - Mudrik, Ivan (Journal of Education, Health and Sport, 2025)
One of the main criteria for evaluating a karate athlete’s technique in competitive conditions is the focused execution of individual phases of competitive exercises, the duration of which depends on the complexity of the overall time structure of the competitive exercise. Goal of research: to investigate the temporal characteristics of the «Sweep-forward-strike» and «Attack from a clinch» competitive exercises performed by karate-do athletes. Research methods used: In this study, we employed the following research methods: theoretical analysis of literature sources, pedagogical observation using instrumental methods of video-biomechanical analysis and multifunctional accelerometry, and statistical methods. The study involved 30 male karate athletes training at the preliminary basic training stage. The results: The results of the pedagogical observation of the rhythm of competitive exercises performed by karate athletes at the preliminary basic training stage are presented. An analysis of the temporal structure of the «Sweep-forward-strike» competitive exercise revealed that athletes perform a pronounced sweep with the attacking foot at a minimal distance from the tatami, which facilitates throwing the opponent off balance. It was established that the exercise structure consists of three phases performed with a sequential decrease in their duration. However, this duration of key points does not correspond to the correct rhythm of this competitive exercise, indicating that athletes focus their efforts on preparatory actions. A study of the temporal structure of the competitive exercise «Attack from a clinch» revealed that athletes spend the most time on phases such as transitioning into a clinch, exiting the clinch, and completing the strike – exiting the attack zone. Conclusions. The data on the analysis of rhythmic patterns in competitive exercises performed by athletes training at the basic preparation stage have been expanded, with an emphasis on the rational distribution of effort during the execution of competitive exercises. Time characteristics have been identified that fully characterize the technique of performing the competitive exercises «Sweep-forward-strike» and «Attack from a clinch» and can be used to monitor the development of technical proficiency in young athletes.